Chia (Salvia hispanica L.): Chemical composition, phenolic compounds, antioxidant activity, and antitumor activity - Tan, Daisy Naomi; Prado, Marcelo Alexandre; Oliveira-Alves, Sheila (Seven Editora, 2024)
The intake of bioactive compounds, such as phenolic compounds and omega 3 fatty acids, from foods of animal and plant origin, is important for protection against chronic non-communicable diseases, such as cardiovascular disease, diabetes, cancer, among others. The increase in cancer incidence is related to changes in eating habits, exposure to pollutants, and factors such as consumption of foods with simple sugars and saturated fats. Studies show that the consumption of natural antioxidants present in fruits, vegetables and vegetable oils can reduce the risk of cancer and other chronic diseases. Chia seed, rich in phenolic compounds and α-linolenic fatty acid, has been linked to benefits such as reducing cardiovascular disease, controlling diabetes, and protecting against oxidative stress. Research on chia seeds seeks to understand its health benefits and its potential in preventing diseases related to metabolic imbalance and chronic inflammation, including cancer. DOI:https://doi.org/10.56238/sevened2024.018-039